2014
DOI: 10.1017/s1478951514000583
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial experiences in the context of life-threatening illness: The cardiac rehabilitation patient

Abstract: Objective: One of the most prevalent life-threatening illnesses is heart disease. The initial trauma of being diagnosed with a life-threatening illness or having a cardiac event can begin a psychosocial chain reaction that results in a transformation of the lives of these patients. The goal of our study was to investigate the lived experiences of psychosocial healing in rehabilitation of cardiac patients using a qualitative written interview.Method: A purposive sample of 14 cardiac event survivors was recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Existential thoughts were described as strong motivators related to patients’ beliefs that exercise could reduce the risk of another cardiac event and to patients’ strong desire to continue to live. A previous study has shown that a heightened awareness of mortality was a motivating factor that led patients with heart disease to make healthy lifestyle changes [24]. On the other hand, the current study also showed that existential thoughts could be regarded as barriers to attending exercise-based CR among patients who wanted to live in the present.…”
Section: Discussionmentioning
confidence: 52%
“…Existential thoughts were described as strong motivators related to patients’ beliefs that exercise could reduce the risk of another cardiac event and to patients’ strong desire to continue to live. A previous study has shown that a heightened awareness of mortality was a motivating factor that led patients with heart disease to make healthy lifestyle changes [24]. On the other hand, the current study also showed that existential thoughts could be regarded as barriers to attending exercise-based CR among patients who wanted to live in the present.…”
Section: Discussionmentioning
confidence: 52%
“…For example, patients described an increase in, and strengthening of, inner resources, as well as a greater ability to function despite their illness. 7,8 Notably, the results of LTCs expanded beyond the circumstances of the illness and positively impacted other difficult life situations such as divorce or career change. 7,8 These LTCs are hypothesized to comprise the process of psycho-social-spiritual healing 9 and are similar to other concepts described in the literature, such as posttraumatic growth and benefit finding.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Notably, the results of LTCs expanded beyond the circumstances of the illness and positively impacted other difficult life situations such as divorce or career change. 7,8 These LTCs are hypothesized to comprise the process of psycho-social-spiritual healing 9 and are similar to other concepts described in the literature, such as posttraumatic growth and benefit finding. [10][11][12] Gender is an important factor in psychosocial and spiritual distress and well-being in patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies in other populations reported a phenomenon wherein participants reported subjective changes in response to life-threatening illnesses, leading to personal growth. 26,27 One hypothesis is that the ability to experience illness in a transformative manner is protective against clinically significant distress. Finally, it is vital to note that even long-term survivors can continue to report ongoing symptoms and the importance of ongoing symptom and needs assessments.…”
Section: Discussionmentioning
confidence: 99%